Perlindungan Hukum Terhadap Hak Cipta Karya Seni Digital Perspektif Hukum Islam - Rizqi Izrul Alamsyah; Rahmawati, Rita (el hisbah Journal of Islamic Economic Law, 2023)
This study aims to analyze how the regulation on Digital Work Copyright in Positive Law in Indonesia and how the legal protection of copyright in digital artwork from the perspective of Islamic Law and Law No. 28 of 2014 concerning Copyright. With qualitative and normative legal methods through a legislative and conceptual approach, which is taken by considering all laws and regulations related to the problem at hand, and a conceptual approach. The results of this study can be concluded that the Regulation on Digital Work Copyright in Positive Law in Indonesia according to Law Number 28 of 2014 can be done in two ways, namely first, preventive protection efforts by protecting copyright starting with warnings and reprimands for perpetrators who commit violations. Second, repressive legal protection where this protection effort is at a more serious stage, namely through dispute resolution. Copyright Legal Protection in Islamic Law Copyright protection (Haqq al-Ibtikar) or ownership in Islamic law can be done in two ways, namely the first is the protection of min Jānib al-Wujūd. Second, the protection of min Jānib Al-Adami